KESIAPAN TUTOR MENGELOLA PEMBELAJARAN DENGAN KURIKULUM MERDEKA PADA PROGRAM KESETARAAN PAKET C DI PKBM CITRA ILMU KABUPATEN SEMARANG - Tisnawati, Narista; Suminar, Tri (Comm-Edu (Community Education Journal), 2025)
The independent curriculum is a new policy that emphasizes differentiated learning and strengthening the Pancasila student profile. Implementation of the independent curriculum requires tutors to be prepared, especially in nonformal education with diverse student characteristics. PKBM (Community Learning Center) needs to ensure tutor readiness so that implementation is not merely administrative but also tailored to student needs. This study aims to describe tutors' readiness in managing learning, starting from understanding the concept of the independent curriculum, planning, implementation, assessment, and challenges faced in the equality program. This study used a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observation, and documentation. The research subjects were Package C1 tutors at PKBM Citra Ilmu. The results showed that tutors have a good basic understanding of the principles of the independent curriculum and have prepared learning plans including CP, TP, ATP, and Teaching Modules. Learning implementation is carried out according to the introduction, core, and closing stages, as well as diagnostic, formative, and summative assessments. On the other hand, the implementation of project-based and differentiated learning is still not optimal due to limited learning facilities and time. Tutor readiness at the Citra Ilmu Community Learning Center (PKBM) is considered quite good in terms of understanding and planning, but still requires ongoing support, training, and adequate facilities for optimal implementation.